SYNTHESIS OF NANOFIBER MEMBRANE FROM WEEE PLASTIC USING ELECTROSPINNING AS AIR FILTRATION MEDIA - Zulfi M, Akmal
The worldwide production of the Waste Electrical and Electronic Equipment (WEEE) plastic waste was reported to reach 54 million tons in 2014 and it increased to 70 million ton in 2017 in which the ABS and HIPS-derived products were the dominant waste. Acrylonitrile Butadiene Styrene (ABS) is one of the most successful engineering of thermoplastic polymers, which is formed from the reaction of three monomers, namely acrylonitrile, butadiene, and styrene. Then, HIPS is a graft copolymer consisting of a small amount of butadiene rubber dispersed in a matrix of polystyrene (PS). In this research we offer the method of ABS and HIPS waste management to become nano fibers membrane with electrospinning technique. The ABS and HIPS membrane is then applied as media of air filtration. Nano fiber is a one-dimensional material which shape is like fine yarns with the diameter of one to several hundred nanometers. The nano fiber has the advantage of having high porosity, low base weight, and wider effective surface. In the air filtration media, this advantage supports for obtaining high efficiency, low pressure drop, and longer lifetime. The system of air filter test for membrane examination consists of several main components: air flow supply and control, filter holder and dummy filter holder, differential pressure sensor, condensation particle counter (CPC), PM2.5 chamber and PSL generator. These equipments are built in a way as to adjust the equipment standards used for air filters testing. The ABS precursor solutions were made by dissolving the ABS waste in three different solvents of DMAc, DMF, and THF with various concentrations of 10, 20, and 30 wt.%. While the HIPS precursor solution were made by dissolving the HIPS waste into the mixture of d-limonene and DMF solvents, the ratios of solvents (dlimonene: DMF) of 3:1, 1:1, and 1:3. The solvent, solution concentration, and the ratios of solvents affected the fiber properties (size and morphology) and membrane properties (wettability, crystallinity, and mechanical properties). Accordingly, we tested the fabricated membranes using SEM, FTIR, XRD, water contact angle, and tensile strength test apparatus. The SEM image depicted three different morphologies, i.e. beads, beaded fiber, and pure fiber. The FTIR spectra showed that the solvents completely evaporated during the electrospinning process. The water contact angle test exhibited the hydrophobic property of all membrane samples. For ABS nanofiber membranes, the XRD spectra showed the amorphous structure of all membranes. The tensile strength test showed that the membranes fabricated using DMF and DMAc solvents had the best mechanical properties. The filtration tests for all membranes depicted that the beads affected the membrane pressure drop and efficiency. The beads gave more space among the fibers, which facilitated the air to flow through the membrane. The beads greatly reduced the pressure drop without overly reduced the membrane filtration efficiency. Moreover, the basis weight of the membrane greatly affected the filtration efficiency. These results have led demonstrated its applicability as a potential air filter media.